Pemanfaatan Hutan Sagu sebagai Sumber Belajar Kontekstual pada Mata Pelajaran IPAS Materi Komponen Biotik dan Abiotik bagi Murid Kelas IV SD Negeri 3 Mimika - Lusia Bolly; Wigati Yektiningtyas; Ode Jamal; Budi Rahayu (Jurnal Ilmiah Telaah, 2026)
This study examines the integration of local wisdom values of the Kamoro Tribe (Mimika Wee) into Natural and Social Science (IPAS) learning for fourth-grade students at SD Negeri 3 Mimika, Central Papua, specifically on biotic and abiotic components. Sago (Metroxylon sagu) is a central element in the lives of the Kamoro people, representing a complex interaction between living organisms (biotic) and their environment (abiotic). This research employs descriptive qualitative methods with an ethnopedagogical approach involving literature review, participatory observation in sago groves, and in-depth interviews with the fourth-grade teacher and Kamoro traditional elders. The findings reveal that: (1) utilizing the sago forest as a contextual learning resource successfully transforms abstract biotic-abiotic concepts into concrete and meaningful learning experiences; (2) the integration of Kamoro ethnoscience effectively enhances student engagement and conceptual understanding; and (3) this approach aligns with the Merdeka Curriculum's demands in fostering the Pancasila Student Profile, particularly the dimensions of faith, piety to God Almighty, and noble character (sub-element of environmental stewardship), global diversity, and mutual cooperation. The implications of this study support the development of locally-contextualized IPAS teaching modules based on local ethnoscience, relevant for students in Papua's coastal regions.